BANDWTIH MANAGEMENT USING "XXX" BANDWIDTH MANAGEMENT WAN ISP IN - Aqwam Rosadi Kardian (Majalah SIKOMTEK, 2006)
Often found that the process of communication and information access data on each userconnected to the BTS was slow, this was due to bandwidth capacity (Line Data) that alreadyexists is not sufficient (over load). Yet when used in accordance with the needs of theexisting bandwidth is sufficient, because of this necessary action to avoid an excessive use ofbandwidth to each user, so that a large bandwidth is used more optimal, efficient and achievethe QOS (Quality Of Service)